Evaluation and performance prediction of a wind turbine blade - Pierce, Warrick Tait (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.